2017
DOI: 10.6002/ect.2017.0007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating mRNA Expression Levels of the TLR4/IRF5 Signaling Axis During Hepatic Ischemia-Reperfusion Injuries

Abstract: Objectives: Hepatic ischemia and reperfusion during liver transplant surgery result in hepatocellular damage. Toll-like receptors, especially TLR4, have a fundamental basic role in the inflammatory phase of ischemia-reperfusion injuries. The effect of the TRIFdependent signaling pathway downstream of TLR4 in hepatic ischemia-reperfusion injury has been well established. However, the role of TLR4-MyD88-dependent signal transduction in hepatic ischemiareperfusion injury has not yet been clarified. The interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“… 49 IRF5 expression is altered in tandem with TLR4 expression following N-acetylcysteine treatment. 50 Our study demonstrated that both the downregulation and upregulation of TLR4 expression in MOVAS cells resulted in similar variations in the expression of TIRAP, MyD88, TRAF6, p38, NEMO, and IRF5. This observation suggests the existence of a potential positive feedback mechanism between TLR4 and its downstream molecules.…”
Section: Discussionsupporting
confidence: 58%
“… 49 IRF5 expression is altered in tandem with TLR4 expression following N-acetylcysteine treatment. 50 Our study demonstrated that both the downregulation and upregulation of TLR4 expression in MOVAS cells resulted in similar variations in the expression of TIRAP, MyD88, TRAF6, p38, NEMO, and IRF5. This observation suggests the existence of a potential positive feedback mechanism between TLR4 and its downstream molecules.…”
Section: Discussionsupporting
confidence: 58%
“…Relative quantification analysis was performed using the 2 −ΔΔCT method. The primers of the Bcl-2 , Bax , Bad and Caspase -3 genes were designed by AlleleID software (Primier Biosoft, USA) and the elongation factor 1 ( Ef1 ) gene was used as a housekeeping gene ( 24 ) ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…IRF1 and IRF5 expression were found to be significantly increased in the liver following exposure to IRI [75,81]. IRF1 had been shown to have a detrimental impact on hepatic IRI by regulating the expression of various inflammatory mediators.…”
Section: Autophagy and Oxidative Stressmentioning
confidence: 98%